Investigating PFAS emissions of light- and heavy-duty fuel cell electric vehicles - T. Lange; M. Dietrich; H. Schlottmann; V. Valkov; V. Mackert; I. Radev; H. Hoster (Journal of Power Sources Advances)
Per- and polyfluoroalkyl substances (PFAS) have been linked to different adverse health effects, highlighting the need to address the examination of all potential emission sources. This also includes applications that are used in key components of the hydrogen economy using proton exchange membranes, e.g. PEM fuel cells. This study analyzes PFAS concentrations in product water from two light- and one heavy-duty fuel cell electric vehicles (FCEV), identifying two to five distinct PFAS (including 6:2 FTS, PFBuA, PFHpA, PFHxA, PFOA, HFPO-DA, and PFPeA) in each sample. However, at this juncture, it is not yet possible to make a well-founded statement as to which components (e.g., MEA or BOP) release these substances.The PFAS concentration was found to be low overall in light-duty vehicles, while in heavy-duty vehicles, elevated levels were observed. Despite these findings, the product water from all vehicles remains within the non-critical range according to current German national PFAS guidelines. However, the results highlight the need for further research and effective strategies to mitigate PFAS emissions from PEM fuel cells in the future.